Scaling Strategies for Industrial Small Tech Firms: Exploring the Market Scaling Process, Barriers, and Outcomes - Garcia Martin, Patricia Carolina; Koporcic, Nikolina; Sjödin, David; Parida, Vinit (Sage publications, 2025)
Scaling is both the main goal and the ultimate challenge for industrial small tech firms (STFs). This is particularly true when firms offer complex and innovative digital solutions for industrial applications. We delineate scaling strategies deployed by STFs, uncovering the underlying configuration of activities driving the scaling process. This study reveals a distinctive sequence, where scaling evolves from a common phase of systematic digital solution piloting, into two distinctive strategies called ecosystem scaling (i.e., solution market evaluation, ecosystem development, and horizontal partner-led scaling activities) and servitization scaling (i.e., customer insights mining, service operations development, and vertical customer-led scaling activities).
Keywords: digital solutions; Ecosystems; scaling strategy; servitization; small tech firms; fi=Strateginen johtaminen|en=Strategic Management|